Applied therapeutics : the clinical use of drugs - Zeind, Caroline S.; Carvalho, Michael G.; Cheng, Judy W. M.; Zaiken, Kathy; LaPointe, Trisha (Philadelphia : Wolters Kluwer Health, 2024)
'Continually revised and updated for 50 years, Applied Therapeutics: The Clinical Use of Drugs is the gold standard for patient centered drug therapeutics. With its acclaimed case-based approach, it promotes mastery and application of the fundamentals of drug therapeutics. Featuring contributions from more than 200 experienced clinicians, every chapter reflects our ever-changing knowledge of drugs and the application of this knowledge to the individualized therapy of patients. As students progress from the General Principles section to chapters on specific diseases, they will benefit from practical problem-solving techniques that help devise effective evidence-based drug treatment plans'--
Includes bibliographical references and index.
Keywords: Drug Therapy